An extremely rare case of rapidly growing mediastinal well-differentiated liposarcoma with a sclerosing variant: a case report - Naoya Iwamoto; Yosuke Matsuura; Hironori Ninomiya; Junji Ichinose; Masayuki Nakao; Yuichi Ishikawa; Sakae Okumura; Mingyon Mun (Surgical Case Reports)
Abstract Background Liposarcoma arising from the mediastinum is rare, accounting for less than 1% of mediastinal tumors. Furthermore, a rapidly growing well-differentiated liposarcoma is extremely rare. A well-differentiated liposarcoma is usually considered a low-grade malignancy. However, we present an extremely rare case of a sclerosing variant of well-differentiated liposarcoma that grew rapidly within a year. Case presentation A 77-year-old man with a giant mass in the left thoracic cavity was referred to our hospital. This mass measured about 10 cm and occupied the left-sided mediastinum on a chest radiography; however, there was no abnormal finding on the previous year’s chest radiography. Chest-enhanced computed tomography revealed a well-circumscribed 11-cm mass in the left-sided anterior mediastinum. Positron emission tomography showed accumulation of fluorodeoxyglucose uptake in this tumor (maximum standard uptake value = 3.3). The radiological findings of computed tomography and positron emission tomography indicated that this tumor was a benign or low-grade malignancy; therefore, the chest radiographic findings were difficult to explain. To explain this discrepancy and establish the diagnosis, tumor resection was performed via left posterolateral thoracotomy. Intraoperatively, the left phrenic nerve and pericardium were adhered tightly to the tumor, so we resected them. The tumor was well-circumscribed and fibrous; therefore, the initial diagnosis was solitary fibrous tumor. However, based on its histopathological and immunohistochemical patterns, the tumor was diagnosed as a sclerosing variant of well-differentiated liposarcoma. Five years postoperatively, the patient remains alive with no evidence of disease recurrence. Conclusions A well-differentiated liposarcoma is usually considered a low-grade malignancy. Nevertheless, the giant tumor in the present case appeared within 1 year. Thus, this was an extremely rare case of a sclerosing variant of well-differentiated liposarcoma with rapid growth.